Public Participation And Tourism Marketing In The Development of Tourism Villages In Bengkulu Province - Darmanto Darmanto; Dwi Kristanti; Siti Aisyah; Heri Wahyudi (Universitas Sultan Ageng Tirtayasa, 2024)
This article aims to examine the development of tourist villages, especially from the perspective of public participation and tourism marketing. Bengkulu is one of the provinces in Indonesia that has natural beauty and attractive tourist destinations; however, the development of its tourist villages has not been optimal in order to improve the welfare of rural communities. From the results of the study, it is hoped that there will be a deep understanding of tourist villages and the problems they face. The method used is comprehensive and systematic qualitative research on the problems of developing tourist villages in Bengkulu. To obtain comprehensive information, interviews were conducted with competent sources in the field of tourism villages in Bengkulu. Research findings show that public participation and tourism marketing in Bengkulu are not as expected. On the other hand, unclear regulations and authority have hampered the implementation of tourism village development in Bengkulu. This article provides lessons on how to optimise public participation and market tourism in a tourist village optimally. Apart from that, it is important to increase cooperation between stakeholders so that tourism village problems can be addressed comprehensively. The author suggests optimising clarity in the management of tourist villages so that people do not find it difficult to participate. It is necessary to ensure that tourism marketing is carried out in a sustainable manner by paying attention to preserving the environment and local culture and providing benefits to local communities.